Research Programs in State Universities in the CALABARZON Area - Aquino, Anania B. (JPAIR Multidisciplinary Research, 2013)
Research is one of the four – fold functions of institutions of higher learning. It is relevant to instruction, extension and production. Relevant to this function, this study assessed the institutional research program of five state universities in the CALABARZON area, Philippines. It made used of the descriptive survey method with the bipolar rating scale questionnaire as the main instrument utilized in gathering data supplemented with interview. The respondents were composed of 59 research administrators and 158 faculty researchers. Faculty researchers are found to be mostly master’s degree holder, assistant professor, regular permanent, with 17 years of teaching experience, have participated in research symposium/seminar/workshop, with seven subject teaching load, and without professional affiliation. Assessment of the institutional research agenda reveals that all seven aspects were rated positive to quite positive as to evaluation; strong to quite strong in terms of potency; and active to quite active in terms of activity. Faculty researchers have also exposed their expectations regarding research production, dissemination and utilization. The study culminated in identifying needs based on the findings on faculty profile, assessment of the institutional agenda and prospects in the institutional agenda. Utilizing these needs, strategies to enhance research production, dissemination and utilization are proposed.